THE DEFINITION OF THE FIRE-EXTINGUISHING EFFICIENCY OF PULVERIZED INDUSTRIAL WASTE - Sh. Shapalov; B. Sapargaliyeva; A. Naukenova; J. R. Ilarri (Academic Journal of Physical and Chemical Sciences, 2019)
Currently, the production of chemical foam fire extinguishers has been canceled, and the main emphasis is on the development of effective powder flame retardant compositions. The standard formulations used are very expensive, so it is promising to study dust-like waste industry due to their low cost, low cost of finalization and the possibility of their utilization. Explosion suppression efficiency of dust waste was determined as follows: the weight of dust fraction < 0.05 mm was weighed on an electronic balance accurate to the fourth digit, and placed in a spray bottle. Further, in the mixer, in a different ratio, a mixture of propane-butane with air is prepared. Then, through the intermediate cylinder, with the help of an electromagnetic valve, the air pulse shoved the canopy and carried the air-gas mixture into a prevacuumed reaction tube. Then, with the help of high-voltage inductor an electric discharge voltage of 1,000 to set to the mixture have been fire. It was shown the examination of the fire-extinguishing ability of expired standard fire extinguishing powders.